Book Review - Dermoscopy Atlas of Facial Melanoses - Deeptara Pathak Thapa (Nepal Journal of Dermatology, Venereology & Leprology)
Handbook of Facial Melanosis by Dr Bibush Amatya is an excellent book worth reading and seems well mounted for post graduate medical students, young Dermatologists and senior consultants alike, who want to improvise their practice with Dermoscopy.